School library projects in Türkiye: A critical view - Demir, Güler (SAGE Publications, 2025)
School libraries are an essential component of education and an indispensable tool in students’ individual, cultural, and social development. In Türkiye, especially with the establishment of the republic, the reforms carried out throughout the country have impacted the development of school libraries, but school libraries have faced many problems. Since 2011, school library projects, mainly led by the Ministry of National Education, have aimed to bring school libraries up to date, but the success of these projects has been controversial. This research critically analyzes the historical context and current state of school libraries in Türkiye through a literature review and evaluation of these projects. Feedback from educators and students underscores the need for improved library spaces and professional development in librarianship. The findings emphasize the necessity for substantial governmental support and the modernization of library facilities to foster a more effective educational environment.